Tratamento de artrite com vitamina D3 livre ou nanoencapsulada: efeito sobre ectoenzimas de linfócitos em modelo animal - Silveira, Karine Lanes da (2014)
Rheumatoid arthritis (RA) is a chronic, multisystem inflammatory disease characterized by symmetric and erosive synovitis. The purinergic signaling system plays an important role in the modulation of inflammatory and immune responses through extracellular biomolecules as nucleotides adenine and its adenosine nucleoside derivative, whose extracellular concentrations are controlled by ectoenzymes action as ecto-nucleoside triphosphate diphosphohydrolase (E-NTPDase) and ecto-adenosine deaminase (E-ADA) present on the surface of various cells. The deficiency of vitamin D, a hormone known to play an important role in calcium homeostasis, has been related the several autoimmune diseases, including RA. This fact is due to its immunomodulatory role, where it inhibits the proliferation of T lymphocytes, especially Th1 lymphocytes as well as in the production and action of cytokines. Due to high doses of vitamin D can lead to hypercalcemia and intoxication it was tested the use of a nanoencapsulation system able to release in a controlled and sustainable manner, a reduced dose on site of action. Based on these principles, the effect of vitamin D3 free and nanoencapsulated was evaluated in the score for arthritis, thermal hyperalgesia and paw edema as well as histological analyzes and in the activity of the E-NTPDase and E-ADA enzyme lymphocytes from animals with arthritis induced by complete Freud‟s adjuvant (CFA). Hematological and biochemical parameters, including serum concentrations of vitamin D, were determined. Adult Wistar rats were divided into ten groups: I: control (CN); II: adjuvant-induced arthritis (AR); III: control vehicle (CV); IV: AR+V; V: vitamin D3 free at a dose of 120 IU/day (VD3); VI: AR+VD3 (120 IU/day); VII: control of white formulation (CF); VIII: AR+F; IX: vitamin D3 lipid-core nanocapsules formulation at a dose of 15.84 IU/day (LNC-D3) and X: AR+LNC-D3 (15.84 IU/day). The initiation of treatment was 15 days after the induction of arthritis in a period of 15 days. The results of this study demonstrated that VD3 was able to reduce arthritis score, thermal hyperalgesia and paw edema in rats with AR. At the same time, treatment with LNC-D3 only reduced thermal hyperalgesia and paw edema. The histological analyzes showed that both formulations were able to reduce inflammatory changes induced by CFA. The levels AST showed an increased in the CN group compared to the others. In the group treated with VD3 it was observed an increase in the levels of 25 (OH)D. The activity of the E-NTPDase in lymphocytes from rats that developed AR was higher in comparison with the control group, whereas the activity of E-ADA was lower. This effect was reversed after 15 days of treatment with VD3 and LNC-D3. In addition, both vitamin D3 formulations did not alter the activity of E-NTPDase and E-ADA enzymes in healthy animals. Data from this study indicate that vitamin D3, either in free or nanoencapsulated forms, seems to contribute mitigating the inflammatory process induced by CFA, possibly by modulating the activities of ectonucleotidases, can be used, after further studies, as a complementary therapeutic agent for the treatment of rheumatoid arthritis.